Design and Construction of an IoT-based Body Mass Index (BMI) Measuring Tool Using an Android Application - Shonya Farha Nabila; Usman Nursusanto (Journal of Robotics, Automation, and Electronics Engineering, 2024)
Body Mass Index (BMI) is a measure of a person's fitness level monitoring obtained from a comparison between weight and height using a separate measuring instrument and requires the energy of other people in the measurement process, namely using a manual meter and scales. Therefore, a height and weight measuring instrument is needed that is integrated into a BMI measuring instrument to determine body health which is categorized into 5, namely, very thin, thin, normal, fat, and obese. The purpose of making this final project is to design the tool, find out the function test, and find out the performance test of the tool. The research stage consists of needs analysis, design, manufacture, and testing of the measuring instrument. The results of this study are that an IoT-based BMI measuring instrument using an android application was successfully created. The results of the function test show that each component is in good condition. While the results of the tool performance test are the same as the application showing that height measurements by ultrasonic sensors and weight measurements by load cell sensors from measurements of 15 people have a good error rate with an average of below 5%, namely 0.64% and 1.50% respectively against manual measurements using standard measuring instruments.